Evaluation of the Major Seed Storage Proteins, the Conglutins, Across Genetically Diverse Narrow-Leafed Lupin Varieties - Tahmasian, Arineh; Juhász, Angéla; Broadbent, James A.; Nye-Wood, Mitchell G.; Le, Thao T.; Colgrave, Michelle L. (Frontiers in Nutrition, 2022)
Lupin seeds have an excellent nutritional profile, including a high proportion of protein and dietary fibre. These qualities make lupin seeds an ideal candidate to help meet the growing global demand for complementary sources of protein. Of consequence to this application, there are nutritional and antinutritional properties assigned to the major lupin seed storage proteins — referred to as α-, β-, δ- and γ-conglutins. The variation in the abundance of these protein families can impact the nutritional and bioactive properties of different lupin varieties. Hence, exploring the conglutin protein profiles across a diverse range of lupin varieties will yield knowledge that can facilitate the selection of superior genotypes for food applications or lupin crop improvement. To support this knowledge generation, discovery proteomics was applied for the identification of the 16 known conglutin sub-families from 46 domestic and wild narrow-leafed lupin (NLL) genotypes. Consequently, the diversity of abundance of these proteins was evaluated using liquid chromatography−multiple reaction monitoring-mass spectrometry (LC−MRM-MS). This comparative study revealed a larger variability for the β- and δ-conglutin content across the lines under study. The absence/lower abundance of the β2- to β6-conglutin sub-families in a subset of the domesticated cultivars led to substantially lower overall levels of the allergenic β-conglutin content in these NLLs, for which the elevation of the other conglutin families were observed. The diversity of the conglutin profiles revealed through this study — and the identification of potential hypoallergenic genotypes — will have great significance for lupin allergic consumers, food manufactures as well as grain breeders through the future development of lupin varieties with higher levels of desirable bioactive proteins and lower allergen content.